Biological control of Hemileia vastatrix berk. & broome with bacillus subtilis cohn and biochemical changes in the coffee - Cacefo, Viviane; de Araújo, Fábio Fernando; Pacheco, Ana Cláudia (Coffee Science - ISSN 1984-3909, 2017)
Hemileia vastatrix stands out as one of the main phytosanitary problems of the coffee culture. The objective of this study was to evaluate the efficiency of the biological control of Hemileia vastatrix and detect some biochemical changes in plants of cultivars Icatu and Mundo Novo treated with foliar spray of Bacillus subtilis and azoxystrobin under field conditions. After the applications, leaves were collected for visual assessment of H. vastatrix severity in accordance with diagrammatic scales. For the biochemical evaluations related to plants defense, leaf tissue samples were collected for the analysis of proline, total phenols, total protein and lipid peroxidation. B. subtilis acted effectively in control of H. vastatrix in both cultivars, but with less efficiency than the azoxystrobin. Plants treated with B. subtilis presented greater proline, total phenols and total proteins in their leaves on the application of azoxystrobin. The cultivar Mundo Novo was more responsive to treatments that Icatu.